Penggunaan Media Pembelajaran Interaktif Berbasis Teknologi untuk Meningkatkan Hasil Belajar PAI Siswa SMKN 9 Padang - Roza Rahma Fitri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education (PAI) using technology-based interactive learning media. The research was conducted in three cycles involving 34 students as research subjects. Each cycle consisted of planning, implementation, observation, and reflection phases. The results showed a significant increase in students' learning mastery. In the pre-cycle, learning mastery reached only 60%. After implementing interactive media, mastery improved to 80% in Cycle I and reached 95% in Cycle III. The success factors include the relevance of the learning media, active student interaction, and the teacher's role as a facilitator. Gamification elements applied in the final cycle also enhanced student motivation. Challenges, such as limited technological facilities and students' adaptation to new media, were addressed through intensive guidance and technical support. The findings indicate that technology-based interactive learning media can serve as an innovative solution to improve the quality of education in the digital era.